2011
DOI: 10.1021/nl103228b
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot-Based Local Field Imaging Reveals Plasmon-Based Interferometric Logic in Silver Nanowire Networks

Abstract: We show that the local electric field distribution of propagating plasmons along silver nanowires can be imaged by coating the nanowires with a layer of quantum dots, held off the surface of the nanowire by a nanoscale dielectric spacer layer. In simple networks of silver nanowires with two optical inputs, control of the optical polarization and phase of the input fields directs the guided waves to a specific nanowire output. The QD-luminescent images of these structures reveal that a complete family of phase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
284
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 280 publications
(287 citation statements)
references
References 44 publications
2
284
1
Order By: Relevance
“…However, the larger difference between CIDs at terminals of another nanowire (c or d) and the illuminating terminal showed that the CID could be manipulated by the chirality of a nanostructure, such as through the coupling angle between two Ag nanowires, the morphology of the Ag terminals, and the distance of the coupling. [6][7][8][9] In this system, the CID increased while the crossing angle was less than 90 6 (terminal c) and Nanowire supported plasmonic waveguide for RE-SERS YZ Huang et al 14 decreased, while the crossing angle was larger than 90 6 . These experimental results demonstrated that the ROA could be remotely excited and enhanced by chiral PSPPs, which had the potential to remotely determine the molecular chirality or the absolute configuration or conformation of a chiral living cell.…”
Section: Raman Optical Activitymentioning
confidence: 76%
See 3 more Smart Citations
“…However, the larger difference between CIDs at terminals of another nanowire (c or d) and the illuminating terminal showed that the CID could be manipulated by the chirality of a nanostructure, such as through the coupling angle between two Ag nanowires, the morphology of the Ag terminals, and the distance of the coupling. [6][7][8][9] In this system, the CID increased while the crossing angle was less than 90 6 (terminal c) and Nanowire supported plasmonic waveguide for RE-SERS YZ Huang et al 14 decreased, while the crossing angle was larger than 90 6 . These experimental results demonstrated that the ROA could be remotely excited and enhanced by chiral PSPPs, which had the potential to remotely determine the molecular chirality or the absolute configuration or conformation of a chiral living cell.…”
Section: Raman Optical Activitymentioning
confidence: 76%
“…[102][103][104][105][106][107][108] We have demonstrated that this enhancement could also be realized through remote SERS of fmoc-glycyl-glycine-OH in an Ag nanowire system in rapid communications (Figure 20). 70 The SEM image and the optical image of the PSPPs present in Figure 20a and 20b indicated that the crossing angle between the nanowires was determined to be approximately 20 6 and released light at the terminals of the nanowire. The local and remote Raman images of fmoc-glycyl-glycine-OH at 1593 cm 21 , excited by left-and right-circularly polarized light, are shown in Figure 20c and 20d, respectively.…”
Section: Raman Optical Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…9,10 Apart from their waveguiding properties, studied extensively by near-field 10,13 and fluorescence-based imaging techniques, [26][27][28] coupled NW structures have been shown to exhibit device functionalities such as nanoscale routers, modulators and logic elements. 12,29 Despite reduced radiative losses, SPPs in chemically prepared NWs still suffer from absorptive losses (on the order of -0.4 dB µm -1 at 800 nm) because of strong confinement. 27 These losses represent an impediment toward the realization of integrated plasmonic circuitry.…”
Section: Subwavelength Confinement and Active Control Of Light Is Essmentioning
confidence: 99%